AN ANALYSIS OF THE OPTIMISATION OF LEAF SPRINGPARAMETERS USING THE ASPECT RATIO-BASEDTAGUCHI-PARETO METHOD - Oluwo , Adeyinka; Alozie , Nehemiah Sabinus; Ogunmola , Bayo Yemisi; Ajibade , Ayomide Tolulope; Rajan, John; Jose , Swaminathan; Oke, Sunday Ayoola (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
This study introduces the aspect ratio Taguchi-Pareto to optimise the leaf spring parameters, using experimental designs and a combination of orthogonal arrays, and signal-to-noise ratios to estimate the optimal parametric settings. Furthermore, the Pareto analysis based on the 80/20 rule created the accepted or rejected experimental trials in the orthogonal arrays. It therefore streamlined the acceptable regions to only the vital signal-to-noise ratios. The research findings reveal that the optimal parametric setting is MA/MLL3MA/NL2MLL/MA3NL/MA3MLL/NL3NL/MLL2. This is interpreted as 0.008426 gcm-3mm-1, 0.565 g/cm3, 113.0876 g-1mm cm3, 0.63532 g-1cm-3, 178 mm, 0.004545 mm-1. The optimal parametric settings obtained enabled the benchmarking of performance standards for the leaf spring inputs while enhancing material usage. Practically, this study offers insights on optimizing leaf spring parameters considering aspect ratios instead of direct parameters. The findings can inform decisions on leaf spring designs and development to improve cost efficiency. Incorporating aspect ratios into the factor and level schemes presents a novel leaf spring design approach, offering a valuable tool for benchmarking and performance evaluation.